NEED ASSESSMENT INOVASI TEAM GAMES TOURNAMENT BERBASIS PERMAINAN TRADISIONAL DALAM PEMBELAJARAN DI SEKOLAH DASAR - Ruchiyat, Marina Gusnia; Herwin; Wuryandani, Wuri; Prihatmojo, Agung (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
This study aims to analyze the need for the integration of the traditional game-based Team Games Tournament (TGT) model in elementary school learning. The method used is qualitative descriptive research with data collection techniques through in-depth interviews, observations, and focused group discussions (FGD) in elementary schools. The results show that both teachers and students express a high need for a more interactive and collaboration-based learning model, where TGT can increase student engagement. Traditional games, which are rich in local cultural values, have been shown to enrich the learning experience and support the development of students' social skills. The main challenge found was the lack of teachers' understanding of how to integrate traditional games in TGT. The implications of these findings are the need to develop learning models that combine TGT and traditional games, as well as training for teachers to optimize their implementation in primary school learning, in order to create more comprehensive and meaningful learning.   Keywords: learning innovation; Team Games Tournament; Traditional Games; Cooperative Learning